Meta-Analisis Pengaruh Model Project Based Learning (PjBL) terhadap Pemahaman Konsep Peserta Didik - Novebrini, Sintya; Asrizal, Asrizal; Mufit, Fatni (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Abstract: This study aims to see the effect size of the project-based learning (PjBL) model on students' understanding of concepts, using the meta-analysis method. The articles obtained in this study amounted to 15 articles. The first result of this research is that the project based learning (PjBL) model has a high category effectiveness on students' conceptual understanding. Second, if it is seen from the level of education, the project based learning (PjBL) model has a high category effectiveness for understanding the concepts of students. The third is the use of project-based learning (PjBL) media that is effectively used for understanding students' concepts. Fourth, science and physics material is effectively used for understanding students' concepts.Intisari: Penelitian bertujuan untuk melihat effect size pengaruh model project based learning (PjBL) terhadap pemahaman konsep peserta didik, dengan menggunakan metode meta-Analisi. Artikel yang diperoleh dalam penelitian ini yaitu berjumlah 15 Artikel. Hasil Penelitian ini pertama yaitu model project based learning (PjBL) memiliki keefektifan kategoti tinggi terhadap pemahaman konsep peserta didik. Kedua yaitu jika dilihat dilihat dari jenjang pendidikan model project based learning (PjBL) memiliki keefektifan kategori tinggi terhdap pemahaman konsep peserta didik. Ketiga yaitu penggunaan media model project based learning (PjBL) efektif digunakan untuk pemahaman konsep peserta didik. Keempat yaitu materi Ipa dan Fisika efektif digunakan terhadap pemahaman konsep peserta didik.